2009
DOI: 10.1080/19396360802626648
|View full text |Cite
|
Sign up to set email alerts
|

Activation of GABAAReceptor/ClChannel and Capacitation in Rat Spermatozoa: HCO3and Clare Essential

Abstract: This study was designed to determine whether HCO 3 À and Cl À are required for the activation of the GABA A receptor/Cl À channel (GBRC) by GABA and the subsequent capacitation of rat sperm. Spermatozoa from adult Sprague Dawley rats were incubated in four different media: modified complete rat fertilization medium (mRFM), Cl À -deficient (Cl À -DF) mRFM, HCO 3 À -DF mRFM, andCl À -DF HCO 3 À -DF mRFM, with or without GBRC agonists (GABA and progesterone) or GBRC antagonists (bicuculline and picrotoxin) for 0-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 61 publications
1
40
0
Order By: Relevance
“…Other cellular ligands can induce the AR such as progesterone (31, 55, 355, 506), ␥-aminobutyric acid (GABA) (280,355,559), glycine (301), EGF (133), ATP (339,442), acetylcholine (66), and sphingosine-1-phosphate (495). The role of many of these "alternative" agonists is not clear.…”
Section: A Generalitiesmentioning
confidence: 99%
“…Other cellular ligands can induce the AR such as progesterone (31, 55, 355, 506), ␥-aminobutyric acid (GABA) (280,355,559), glycine (301), EGF (133), ATP (339,442), acetylcholine (66), and sphingosine-1-phosphate (495). The role of many of these "alternative" agonists is not clear.…”
Section: A Generalitiesmentioning
confidence: 99%
“…Moreover, P-enhanced hyperactivation is competitively suppressed by 17β-estradiol (E) [18]. In rat spermatozoa, P and GABA increase hyperactivation through the GABA A receptor/Cl - channel [19]. …”
mentioning
confidence: 99%
“…In humans, rams and rats, GABA appears to increase sperm hyperactivation via the GABA A receptor/Cl - channel [19,20,21,22]. Because the GABA A receptor is the Cl - channel, it is thought that hyperactivation is increased through activation of the Cl - channel and hyperpolarization by Cl - influx [19, 20].…”
mentioning
confidence: 99%
“…For example, Ritta et al established that this neurotransmitter plays a role in the regulation of motility in bovine and human sperm (Ritta et al 2004 ;Ritta et al 1998 ). In rat sperm, GABA and progesterone accelerated the process of capacitation and hyperactivated motility, effects that were inhibited by bicuculline and picrotoxin (Jin et al 2009 ). Additionally, it has been shown that GABA can induce the AR (Puente et al 2011 ;Shi et al 1997 ) and also that GABA A receptors can modulate the response to progesterone in these cells (Hu et al 2002 ;Ritta et al 1998 ;Shi and Roldan 1995 ;Turner et al 1994 ).…”
Section: Gaba and Glycine Receptorsmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) and immunocytochemistry studies revealed the presence of GABA A and GABA B receptors in spermatogenic cells, and patch-clamp studies showed that GABA application to round spermatogenic cells induced an inward Cl − current (Kanbara et al 2011 ). The presence and function of GABA A receptors in sperm from different species have been explored by several laboratories (Jin et al 2009 ;Meizel 1997 ;Puente et al 2011 ;Wistrom and Meizel 1993 ). For example, Ritta et al established that this neurotransmitter plays a role in the regulation of motility in bovine and human sperm (Ritta et al 2004 ;Ritta et al 1998 ).…”
Section: Gaba and Glycine Receptorsmentioning
confidence: 99%